The Impact of ESG Performance on Firm Value with Moderation of Corporate Sustainable Growth Rate (Study on JII Indexed Companies for the 2021-2023 Period) - Lestari, Nimas Dewi; Wahyuni, Nanik; Meldona, Meldona (ITB AAS INDONESIA Surakarta, 2024)
The value of a company reflects investors’ perception of the effectiveness of management in utilizing the company's resources in the present and future. This study aims to investigate the impact of environmental, social, and governance (ESG) performance, as represented by ESG Risk Rating, on firm value, with the sustainable growth rate (SGR) acting as a moderating factor. The study adopts a quantitative approach, using the moderated regression analysis (MRA) method. The research focuses on companies listed on the Jakarta Islamic Index (JII) during the 2021-2023 period. The findings indicate that ESG performance significantly influences firm value, and the sustainable growth rate (SGR) can moderate the relationship between ESG performance and firm value for companies listed on the JII during the 2021-2023 period. This study concludes that the level of ESG performance of companies proxied by ESG Risk rating is one of the factors that must be considered in making investments. In addition, the company's sustainability growth rate is important when making investments in the long term. This research provides important implications for company management and investors in making strategic decisions related to ESG and sustainable growth so that they can achieve optimal long-term value.